(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Plant diseases can be defined as abnormal changes in physiological processes that permanently disturb the normal activity of plant organs (Julius Kuhn, 1858). Horsfall and Diamond (1959) described plant diseases as a “malfunctioning process in the plant body due to continuous irritation which results in suffering producing symptoms.” A plant is specifically termed ’diseased’ only when its malfunctioning process involves association with a pathogen. All plant diseases result from a three-way interaction between a susceptible host, a virulent pathogen, and a favorable environment. An epidemic develops if all three of these factors are conducive to disease development. Recently, two more components have been added to this triangle after evaluating their significant role in disease development: time and human activity. Principally, all plant diseases can be controlled by manipulating one or more of these factors to create conditions unsuitable for the replication, survival, or infection by the pathogen.